Nutrient Uptake, Partitioning, and Production of Two Subspecies of Brassica using Different Solution Concentrates in Floating Hydroponics Systems - Mercy Bientri Yunindanova; Subuh Pramono; Muhammad Hamka Ibrahim (Buletin Agroteknologi, 2020)
In this study, we investigated nutrient uptake, partitioning, and production of two subspecies of Brassica in response to nutrient solution concentration in floating hydroponics systems. This study used a complete randomized block design factorial with two factors. The first factor was two Brassica subspecies consisting of Brassica rapa subsp. chinensis (Pak Choi) and Brassica rapa var. parachinensis (Choy Sum). The second factor was the concentration level consisting electrical conductivity (EC) 1 mS cm-1 and EC 2 mS cm-1. The results indicated the absorption rates of nitrogen (N,) phosphorus (P), and potassium (K) in leaves, roots and stems were similar in both nutrient concentrations. In general, all combination treatments resulted more accumulation of P followed by N, also K as the smallest proportion. P was mostly accumulated at the root and leaves (19.60 to 25.90 mg g-1), while majority of N was collected in leaves ranging from 18.00 to 24.30 mg g-1. The highest K content was detected in the stem (10.70 to 14.20 mg g-1). P uptake was 1.69 to 2.47 times higher than K, while N uptake was 1.44 to 2.04 times higher than K. Both two subspecies and concentrations performed no significant effects on nutrient uptake. Although same species, the plant growth parameters of Pak Choi and Choy Sum are very different including plant height, leaves number, width and length. Both two subspecies adapted well with both concentrations. However, significant differences were recorded in the combination of subspecies and nutrient concentration on plant growth and production parameters. To achieve higher market portion, Pak Choi would be more suitable to be planted on EC 1 mS cm-1, while Choy Sum was favorable at both concentrations.